Force-closure orchard dexterous hand grasping model - Bao, Xulan; Ren, Mengtao; Ma, Xiaojie; Chen, Biyu; Bao, Yougang; Mao, Jincheng (International Journal of Agricultural and Biological Engineering, 2025)
The digital orchard is an important trend for the future development of orchards towards intelligentization. The current wide variety of orchard gripping objects with different sizes and material characteristics brings challenges for gripping operations. In order to improve the versatility and dexterity of the orchard end-effector, a humanoid 14-degree-of-freedom orchard dexterous hand is designed for agronomic operations. An optimal design scheme of the orchard dexterous hand combining orchard gesture analysis and human hand structure is proposed, and the design of the modular fingers, palm, and overall structure of the orchard dexterous hand is completed. The orthogonal and inverse kinematics model of the dexterous hand is established to analyze the motion space of the fingertips, and the dexterity of the orchard dexterous hand is verified by combining with the Kapandji test. The equivalent distribution model of the contact force is solved according to the Hertz theory, and the grasping matrix is established based on the friction surface contact model to realize force-closure, which describes the relationship between the finger and the object being grasped in the configuration. The experimental platform of dexterous hand in the orchard is built, and the experiments of gesture formation, grasping, and contact force testing are carried out. The results show that the dexterous hand can form all kinds of gestures commonly used in the orchard and can grasp spherical fruit with diameters of 26-90 mm, masses of 11-238 g, and all kinds of orchard-specific working tools; for navel oranges with masses of 234 g, the dexterous hand can realize stable grasping under different gestures. This provides a theoretical basis and technical support for the realization of complex agronomy in orchards. Keywords: digital orchard, dexterous hand, orchard gesture, force-closure DOI: 10.25165/j.ijabe.20251804.8925 Citation: Bao X L, Ren M T, Ma X J, Chen B Y, Bao Y G, Mao J C. Force-closure orchard dexterous hand grasping model. Int J Agric & Biol Eng, 2025; 18(4): 139–148.